E.X.O. : the legend of Wale Williams. Volume two - Okupe, Roye; Okupe, Roye (Dark Horse Books, 2022)
"E.X.O. Volume 2 picks up right where it's award-winning Afrofuturist epic predecessor left off, as Wale Williams--aka tech-savvy superhero EXO--tries to save humanity! An Afrofuturist superhero story about redemption set in the bustling metropolis that is Lagos, Nigeria--with a creative team that's also from Lagos!"--Amazon.